2002
DOI: 10.1152/ajpendo.00071.2002
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-induced osteogenesis in intact female mice lacking ERβ

Abstract: We recently found that estrogen receptor (ER) antagonists prevent highdose estrogen from inducing the formation of new cancellous bone within the medullary cavity of mouse long bones. In the present investigation, we studied the role of specific ER subtypes in this response by examining whether this is impaired in female ER␤ Ϫ/Ϫ mice previously generated by targeted gene deletion. Vehicle or 17␤-estradiol (E 2) (range 4-4,000 g ⅐ kg Ϫ1 ⅐ day Ϫ1 ) was administered to intact female ER␤ Ϫ/Ϫ mice and wild-type lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…The finding that the bone protective effect of C. comosa is mediated through ER␣ is in agreement with the previous study showing that bone formation stimulated by estrogen requires the presence of ER␣ (McDougall et al, 2003). In addition, McDougall et al demonstrated in ER␤ -/− mice that ER␤ did not mediate the osteogenic response to estrogen (McDougall et al, 2002). However, the molecular mechanism by which diarylheptanoid compounds protect bone mass requires further studies.…”
Section: L5-6 Femur Tibiasupporting
confidence: 91%
“…The finding that the bone protective effect of C. comosa is mediated through ER␣ is in agreement with the previous study showing that bone formation stimulated by estrogen requires the presence of ER␣ (McDougall et al, 2003). In addition, McDougall et al demonstrated in ER␤ -/− mice that ER␤ did not mediate the osteogenic response to estrogen (McDougall et al, 2002). However, the molecular mechanism by which diarylheptanoid compounds protect bone mass requires further studies.…”
Section: L5-6 Femur Tibiasupporting
confidence: 91%
“…It is well documented that physiological estrogens suppress bone turnover but that high-dose estrogen treatment increases bone formation and is strongly anabolic (65)(66)(67). Similarly, it is also well accepted that glucocorticoids increase osteoblastogenesis in vitro (68 -73), whereas continuous in vivo exposure decreases osteoblastogenesis, increases osteoblast apoptosis, and increases osteoclast activity leading to bone loss (38, 74 -78).…”
Section: Discussionmentioning
confidence: 99%
“…Adult mice killed by cervical dislocation were analyzed by dual-energy-X-ray absorptiometry (DXA) using a PIXImis scanner (Lunar, Madison, WI) with small-animal software, as previously described (40). The parameters that were evaluated included total area, lean tissue weight, and fat tissue weight.…”
Section: Methodsmentioning
confidence: 99%